ATTITUDES AND PERCEPTIONS OF RELATIONSHIPS WITH COMMITMENT DEPOK CITY COUNCIL MEMBERS ABOUT THE PROTECTION AND FULFILLMENT OF CHILDREN'S RIGHTS - Deni Agnes Darmawati; Zarfiel Tafal (JOURNAL OF LAW AND GOVERNMENT SCIENCE, 2015)
Depok city became a stopover town and has various problems such as street children’s, dropouts and don’t have local regulations concerning the protection of children. Efforts to improve the protection of children in need of care and commitment Depok City Council members to make or submit a local regulation draft in Depok.Methods: This study aims to determine the factors related commitments Depok City Council members about the protection and fulfillment of children's rights. The research was conducted in Depok City Council for 3 months with 30 respondents Depok city parliament. Quantitative research that uses non-experimental design, the data obtained by cross sectional. Statistical tests were performed chi square to see the relationship between two variables.Results: According to the result of statistical analysis, there is significance correlation between attitudes and perceptions of Depok City Council members about the protection and fulfillment of children's rights (p value = 0.002 and OR = 16 875). There is a significance correlation between perception and commitment to the protection and fulfillment of children's rights (p Value = 0.002 and OR = 28)Conclusion: Lack of commitment Depok city parliament characterized by negative attitudes and less perceptions. So we need communication, information, education and advocacy intensively on the protection and fulfillment of children's rights.Key Words: Children’s rights, parliament